FORMAL MODELS AND ALGORITHMS IN POLITICAL SCIENCE: GAME-THEORETIC APPROACH - A. A. Vartumyan; I. S. Klimenko (Современная наука и инновации, 2022)
The issues of interdisciplinary integration of research methods of political processes are of particular interest from both theoretical and practical points of view. Application of methods of system analysis, decision theory, mathematical and simulation modeling to the study of political, socio-economic systems is a non-trivial task that allows you to identify patterns and trends in the development of systems with behavior, gain experience in forecasting and comparative analysis of research results. The article presents the results of the research, the subject of which is to determine the conditions for the applicability of the game-theoretic approach to the study of political processes. The article is devoted to the game-theoretic approach in the study of political processes. The authors define the possibilities that open up the application of game theory to the analysis of complex systems with behavior. According to the authors, the relevance of the research topic is determined by the insufficient attention of the scientific community to the tools that representatives of exact Sciences are ready to provide to political scientists and sociologists. The current state of formal modeling in political science is at the stage of initial definition of the subject of research and formation of the concept.